Transcriptome Sequencing Identifies PLAUR as an Important Player in Patients With Dermatomyositis-Associated Interstitial Lung Disease - Chen, Juan; Zhang, Ruixian; Xie, Min; Luan, Chunyan; Li, Xiaolan (Frontiers in Genetics, 2021)
Dermatomyositis (DM), an inflammatory disorder, is often associated with interstitial lung disease (ILD). However, the underlying mechanism remains unclear. Our study performed RNA sequencing (RNA-seq) and integrative bioinformatics analysis of differentially expressed genes (DEGs) in patients with DM-ILD and healthy controls. A total of 2,018 DEGs were identified between DM-ILD and healthy blood samples. Gene ontology (GO) and Kyoto encyclopedia of genes and genomes (KEGG) pathway enrichment analysis showed that DEGs were mainly involved in immune and inflammatory related biological processes and pathways. Disease ontology (DO) enrichment analysis identified 35 candidate key genes involved in both skin and lung diseases. Meanwhile, a total of 886 differentially expressed altenative splicing (AS) events were found between DM-ILD and healthy blood samples. After overlapping DEGs with differentially AS genes, plasminogen activator, urokinase receptor (PLAUR) involved in immune-related biological processes and complement and coagulation cascades, was screened and identified as the most important gene associated with DM-ILD. The protein-protein interaction (PPI) network revealed that PLAUR had interactions with multiple candidate key genes. Moreover, we observed that there were significantly more neutrophils and less naive B cells in DM-ILD samples than in healthy samples. And the expression of PLAUR was significantly positively correlated with the abundance of neutrophils. Significant higher abundance of PLAUR in DM-ILD patients than healthy controls were validated by RT-qPCR. In conclusion, we identified PLAUR as an important player in regulating DM-ILD by neutrophil associated immune response. These findings enrich our understanding, which may benefit DM-ILD patients.